POLYETHERSULFONE COMPOSITE MEMBRANE BLENDED WITH CELLULOSE FIBRILS - Ping Qu; Huanwei Tang; Yuan Gao; Liping Zhang; Siqun Wang (BioResources, 2010)
Polyethersulfone (PES) is a common material used for ultrafiltration (UF) membranes, which has good chemical resistance, high mechanical properties, and wide temperature tolerances. The hydrophobic property of the PES membrane seriously limits its application. Cellulose ﬁbrils are composed of micro-sized and nano-sized elements, which have high hydrophilicity, strength, and biodegradation. A composite membrane was prepared by the phase inversion induced by an immersion process. The characteristics of the composite membrane were investigated with Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), thermogravimetric analysis (TGA), and atomic force microscopy (AFM). The pure water flux of the composite membrane increased dramatically with the increase of cellulose firbils. Mean pore size and porosity were significantly increased. Both mechanical properties and hydrophilicity were enhanced due to the addition of the cellulose firbils.